Optimizing Preventive Maintenance to Improve Operational Efficiency and Reduce Maintenance Costs - Review Article - Ilham, Muhammad; Mainil, Rahmat Iman (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2025)
The Total Productive Maintenance (TPM) approach is one of the main operational strategies to improve production efficiency and reduce maintenance costs. This article reviews the important role of TPM components, especially the Planned Maintenance System (PMS) and Computerized Maintenance Management System (CMMS), in supporting operational performance. The implementation of these systems involves structured data collection and systematic analysis to improve predictive and preventive maintenance. This article also highlights the success factors and obstacles to implementing TPM, PMS, and CMMS, including management commitment, employee training, technology integration, and challenges such as resistance to change and system complexity. The review results show that cross-functional collaboration, a continuous improvement mindset, and the use of advanced technology are the keys to success in optimizing equipment maintenance, reducing downtime, and increasing operational efficiency and cost effectiveness. Across reviewed studies, operational efficiency increased by 12–35% and maintenance costs decreased by 10–30% after adopting TPM, PMS, or CMMS. These findings emphasize the critical role of digital integration and proactive culture in maintenance optimization.